An equalization charger based on phase‐shift full‐bridge converter with an n‐stage current rectifier. (17th January 2022) - Yang, Xiaoguang; Wang, Dexin; Jia, Zhe; Su, Yukui; Zhao, Xiaobing; Nie, Baoxin
Summary: A traditional charging system is composed of a charger and a separate voltage equalizer. By integrating the voltage equalization circuit into the charger as an equalization charger, the components can be reduced, and the system can be simplified. The equalization charger consists of two functional parts: The front stage generates a PWM voltage wave, and the rear stage generates multiple uniform output voltages. In this paper, a new n ‐stage current rectifier (CR) is proposed as the rear stage, which has higher power conversion efficiency than traditional voltage multipliers. The full‐bridge (FB) converter is selected as the front stage and combined with the n ‐stage CR to form a phase‐shift (PS) FB converter, which can realize zero voltage switching (ZVS) operation under light load conditions. The basic working principle of the equalization charger is described, and analytical models for converter design are derived. A prototype for three battery modules was built and tested under the condition of initial voltage unbalance. Experimental results show that the proposed equalization charger has good voltage equalization characteristics, and the standard deviation is as low as about 4 mV. Experimental results show that all switches can achieve ZVS under light load conditions. Abstract : By integrating the voltage equalization circuit into the charger as an equalization charger, the components can be reduced, and the system can be simplified. In this paper, a new n ‐stage current rectifier is proposed as the rear stage of the equalization charger, and the full‐bridge converter is selected as the front stage. The proposed equalization charger has good voltage equalization characteristics and high efficiency. Experimental results also show that all switches can achieve ZVS under light load conditions.